Capitalism and Revolution in Caio Prado Jr - Del Roio, Marcos (Pontifícia Universidade Católica de São Paulo, 2016)
This article offers some clues for explaining why Caio Prado Jr. became the most influential Brazilian Marxist of what could be called the classical era, which ended with the April 1964 military coup. In the 1970s we can see the entrance into the academy of Caio Prado Jr.’s studies on Brazilian reality, to the point that they came to dominate discussions among Marxists and those who use Marxism as an analytical reference point. Caio Prado Jr.’s analysis suggests an interpretation grounded in the category of the colonial system, with an emphasis on the circulation of goods and an economistic and positivistic perspective. These last two elements are common to Brazilian Marxism of the formative and classical period (1920-1964).